AB0242 The evaluation of methotrexate related lymphoproliferative disease. (23rd January 2014) - Mukai, M.; Kanda, M.; Kondo, M.
Abstract : Background: It is well known that EB virus related lymphoproliferative disease (LPD) is related with immunosuppressive treatment. It has been reported that EB virus related LPD developed in the patients with rheumatoid arthritis (RA) treated with methotrexate (MTX). Objectives: As MTX doses for RA in Japan was limited to 8 mg/week until 2011, we evaluated the clinical character of MTX related LPD in our hospital. Methods: We retrospectively picked up the MTX-related LPD cases from our patients since 2002. Results: Ten cases of MTX related LPD were found, 9 RA and 1 dermatomyositis. The ratio of male to female was 3:7. The average age of onset of LPD was 67.8±9.1 years old. The average duration of administration of MTX was 67.0±38.2 months (30-147 months). Average dose of MTX was 8.0±1.7 mg/week (6-12 mg). Corticosteroid was used in 5 cases, and 4 cases with RA were treated with 5 mg/day, and a case with dermatomyositis was treated with 10 mg/day. Biologics were administered in 5 cases, and all was infliximab. Folic acid was used in 4 cases. The pathology showed that 7 cases were diffuse large B cell lymphoma, 2 cases were Hodgkin's disease, and one unknown case was included. EB virus was demonstrated in 9 cases. The origins of LPD indicated that 3 cases were lymph nodes and 7 cases were extralymphatic site such as subcutaneous, stomach, adrenal grand, or lumbar spine. The prognosis were different in each case: LPD was disappeared after the discontinuance of MTX in 5 cases, clinical remission was achieved with radiation to lumbar spine and chemotherapy including rituximab in a case (but, he was dead by lung cancer 3 years later), relapse after chemotherapy including rituximab in a case with Hodgkin's disease, dead during chemotherapy in a case, and dead after relapse during treatment rituximab. Conclusions: MTX related LPD could be occurred in patients with long period of treatment with MTX, but not related with the dose of MTX. It could be occurred with severe type of RA who needed biologic agents. EB virus could be demonstrated in the tissue. The location of LPD was much more in extralymphatic site than in lymph node. Many cases showed diffuse large B cell lymphoma type. MTX related LPD was disappeared in many cases by stopping MTX, but some case showed relapse. In our case, the prognosis in the cases treated with rituximab was showed as very poor because of unknown reason. Disclosure of Interest: None Declared